2014
DOI: 10.1177/0957650914525611
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on chemical recuperation using hybrid dielectric barrier discharge-catalytic methane-steam reforming

Abstract: Hybrid dielectric barrier discharge-catalytic steam reforming is proposed here for use in chemically recuperated gas turbines, so as to be compatible with the low-temperature exhaust heat from turbines. Four different types of reactor were designed for comparison, and extensive experiments were performed to evaluate the exhaust heat recovery in terms of effective carbon recovery rate, methane conversion, fuel heating value increase rate, and total enthalpy increase rate. The effect of methane space velocity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
1
1
1
Order By: Relevance
“…Further, compared to previous work, 6 the selectivity towards CO and C 2 H 6 is found to enhance with the presence of β-Ga 2 O 3 . Although Liu et al reported a 100% selectivity for H 2 , the yield was only 20.14%, 61 which is lower compared to the H 2 yield (30%) obtained by plasma alone in the current work. Furthermore, they observed the reaction to be highly selective toward CO 2 (60% selectivity), whereas we did not observe CO 2 formation.…”
Section: Resultscontrasting
confidence: 81%
“…Further, compared to previous work, 6 the selectivity towards CO and C 2 H 6 is found to enhance with the presence of β-Ga 2 O 3 . Although Liu et al reported a 100% selectivity for H 2 , the yield was only 20.14%, 61 which is lower compared to the H 2 yield (30%) obtained by plasma alone in the current work. Furthermore, they observed the reaction to be highly selective toward CO 2 (60% selectivity), whereas we did not observe CO 2 formation.…”
Section: Resultscontrasting
confidence: 81%
“…A similar phenomenon was also observed by Liu et al. [ 314 ] These results demonstrate that plasma‐catalytic coupling is a feasible strategy to improve the efficiency of PASMR systems, and more research is needed in the future.…”
Section: Application Of Plasma Technology For Different Ch4 Reforming...supporting
confidence: 85%
“…Chemically recuperated gas turbine (CRGT), as a promising advanced cycle gas turbine, can greatly improve gas turbine thermal efficiency and reduce NOx emission. , In the past decades, many scholars have done a lot of experimental and theoretical work on CRGTs. The CRGT concept is shown in Figure . Turbine exhaust is cascaded utilized by steam reformer (SR) and steam generator (SG), respectively.…”
Section: Introductionmentioning
confidence: 99%